Thermal and Mechanical Properties of Clay and Drop-Off of Ceiba Pentandra (Kapok) Plant Wool Mixture - Abdulrahim, A. T.; Abdulkareem, S.; Abdulraheem, S. A.; Mohammed, W. J. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This study is aimed at the investigation of the effects of the addition of clay to drop-off of Ceiba pentandra (Kapok) plant wool on the thermal and mechanical properties of the materials produced. Because of the considerable increase in the use of insulations in many heat devices, process and systems, and dependence on imported insulations, the need to process natural fibre insulations to form rigid or semi-rigid material using appropriate and sustainable binding material cannot be over emphasized. For this study, Kapok wool and clay mixture were investigated. Five samples were prepared: Sample A was 100% Kapok wool while samples B, C, D, and E were mixture of Kapok wool and Clay in water with varying percentage of clay quantities (Kapok to Clay ratio; B 2:1, C 2:1.5, D 2:2.5, E 2:3.5). The samples were prepared into cylindrical shapes, compressed and dried. The Thermal conductivity meter on Armfield Heat transfer equipment was used to find the thermal conductivity of each sample, while the thermal diffusivity and thermal resistivity of samples were determined using appropriate formula. Universal Testing Machine (Model: FS 50AT) was used to determine the stress at Yield and Young Modulus of elasticity for samples B, C, D, and E. Results show that the density of sample increases with increase in clay content. Thermal conductivities of the samples after the addition of clay ranges between 0.027 (W/mK) and 0.013 (W/mK). Reversed was the case for Thermal Resistivity, the value of thermal resistivity first decreases with addition of clay content (sample B) and then started increasing with increased clay content in the samples, and the values range from 37.037 to 76.923mKW-1. Thermal diffusivity of sample decreases from 1.2762 x10-3 m2/s to 0.2810 x10-3 m2/s with increasing clay content. Results also show that the Stress at Yield of samples range from 0.012 N/mm2 to 0.022 N/mm2 while the Young Modulus of elasticity range from 0.113 N/mm2 to 0.222 N/mm2. Kapok wool – Clay combination of ratio 2:3.5 (Sample E) have the highest value of thermal resistivity and lowest thermal diffusivity, though with high density, which suggests it to be the best among samples in the study for insulation purposes. The products are recommended for use as insulations of thermal storage for medium temperature applications.